Internationale Nachwuchswissenschaftler in Deutschland Motivation - Integration - Förderung. Ergebnisse einer bundesweiten Studie - Wegner, Antje (Schriftenreihe Hochschulmarketing, 2016)
"What motivates international scientists to research and teach at German Universities? How successful is their professional and social integration? What are their long-term career objectives? The MIND study at GATE-Germany (a consortium for international university marketing funded by DAAD and HRK) comprehensively surveyed international post-doctoral academics for the first time on their decision motivation, organisational challenges and their professional and social integration across all participating universities. The resulting quantitative data delivers empirical information about needs and decision criteria of young, post-doctoral academics and therefore expands the experience knowledge of the universities."